Interventions for Perinatal Depression and Anxiety in Fathers: A Mini-Review - Rodrigues, Andre L.; Ericksen, Jennifer; Watson, Brittany; Gemmill, Alan W.; Milgrom, Jeannette (Frontiers in Psychology, 2022)
Up to 10% of fathers experience perinatal depression, often accompanied by anxiety, with a detrimental impact on the emotional and behavioural development of infants. Yet, few evidence-based interventions specifically for paternal perinatal depression or anxiety exist, and few depressed or anxious fathers engage with support. This mini-review aims to build on the evidence base set by other recent systematic reviews by synthesising more recently available studies on interventions for paternal perinatal depression and anxiety. Secondarily, we also aimed to identify useful information on key implementation strategies, if any, that increase the engagement of men. We drew upon 3 major previous systematic reviews and performed an updated database search limited to trials, feasibility studies or pilot studies of interventions published between 2015-20 that reported on fathers’ perinatal mental health. We included psychological, educational, psychosocial, paternal, couple-focused, or group therapies that reported on either paternal depression, anxiety or both. Eleven studies satisfied search criteria (5 of which were not included in previous reviews). The majority were randomised controlled trials. Most interventions incorporated counselling, therapy or psychoeducation and took an indirect approach to perinatal mental health through couple-focussed education. No studies reported a presence of diagnosed depression or anxiety at baseline, although five studies reported a positive effect on symptoms. No studies targeted the explicit treatment of clinically depressed or anxious men; the most substantial gap in the evidence base. There is a need to deliver perinatal interventions specifically designed for men and evaluate them in populations with clinical levels of symptomatology.